Principios básicos de la ciencia y tecnología de alimentos - Valdivia-Barra, Tatiana (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2023)
Food science implies a complex understanding of the matter from a chemical and biological approach, which is why it is based on a series of disciplines, such as chemistry, biochemistry and microbiology, to approach it in a comprehensive manner. "Basic principles of food science and technology" is a text that constitutes an instrument of university orientation, for undergraduate students. Thematic contents are elementary concepts that guide a specific academic and technical training, given the practical application of its content.